The Role of Self-Efficacy and Technology Upon the Participation of Men in Healthy Lifestyle Behavior - Maxwell, Karen Denise; Gerrior, Shirley; Crawford, Kermit (British Journal of Healthcare and Medical Research, 2022)
Few health interventions are targeted exclusively to men. Limited knowledge exists regarding the specific components needed to design Internet health applications to appeal to men. This study examined the relationship between the use of Internet health applications and the role of self-efficacy in men and the influence upon participation in health and wellness behaviors, such as diet and physical activity. A quasi-experimental design was used to analyze data collected from the National Cancer Institute’s (NCI) Health Information National Trends Survey (HINTS). A group of men (N=990) who used Internet health applications were compared to a control group of men who did not use Internet health applications. Results from the regression analysis indicated that the use of Internet health applications for self-management of health behavior had a significant effect upon participation in health and wellness behavior t (49) = -2.212, < .05. Self-efficacy was found to have a greater significant effect upon participation in health and wellness behavior than Internet health applications t (49) = -2557, p < .05. Self-efficacy mediated the relationship between Internet health applications and participation in health and wellness behavior t (48) = -2.744, p < .05. The results of this study offer support for the efficacy of operationalized applications as an evidence-informed user-driven resource for men. Consequently, designing Internet health applications which include the theoretical foundation, self-efficacy could significantly increase the participation of men in health and wellness behaviors.